Stable carbon, nitrogen and sulphur isotope analysis of permafrost preserved human hair from rescue excavations (2009, 2010) at the precontact site of Nunalleq, Alaska. (February 2018) - Britton, Kate; McManus-Fry, Ellen; Nehlich, Olaf; Richards, Mike; Ledger, Paul M.; Knecht, Rick
Abstract: The reconstruction of diet and subsistence strategies is integral to understanding hunter-gatherer societies in the past, and is particularly of interest in high latitude environments as they can illuminate human-environmental interactions and adaptations. Until recently, very little archaeological research had been undertaken on the Bering Sea coasts of the Yukon-Kuskokwim Delta, and relatively little is known about precontact lifeways in this region. Here, we present stable carbon, nitrogen and sulphur isotope data from non-mortuary human hair excavated from Nunalleq (c. 1300 CE–1750 CE) – a precontact village site in Western Alaska. Now the focus of a major research project, excavations at Nunalleq began as a rescue excavation, as the site is eroding rapidly into the Bering Sea. Following an initial pilot study on cut strands representing a small number of individuals, a larger body of isotope data has now been generated from the first phase of the investigations of Nunalleq (2009, 2010). These new data, including sulphur isotope values, provide further evidence for the subsistence strategy at the site, including a mixed diet of marine and terrestrial foods (but likely dominated by salmonids). In addition, these new data from Nunalleq highlight some dietary variability amongst the inhabitants of the site. Analyses of additional longer hair strands suggest this variability may not be exclusively due to seasonal variation, and may evidence inter-personal dietary differences. Data from Nunalleq are compared to isotope data from previous studies of Thule-era and earlier Alaskan sites, and to isotope data from Thule sites in Canada and Greenland and the potential of ongoing and future research at the site is discussed, along with the implications for our understanding of Thule subsistence strategies and precontact lifeways on the Yukon-Kuskokwim Delta. Highlights: Human hair is preserved at the precontact site of Nunalleq, Western Alaska, allowing high-resolution dietary reconstruction. Diet includes a mix of marine, riverine and terrestrial foods, and was likely dominated by salmonids. Sulphur isotope analysis further supports the data from the carbon and nitrogen analysis. The analysis of longer hair strands reveals intra- (and inter-) annual and inter-individual variability. The data, in combination with those from previous studies, highlight variability in Thule-era diet across the North American Arctic and Greenland.